Designing E-book for The Practical Experiment Course of Chemistry Teaching Method for Students of University of Science and Education – The University of Da Nang
Báo cáo Tổng kết Đề tài Nghiên cứu Khoa học và Công nghệ cấp Đại học Đà Nẵng; Mã số: B2017-ĐN03-06; 129 trang.